2014
DOI: 10.14257/ijunesst.2014.7.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Waste Tire as an Asphalt Cement Modifier for Road Pavement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Waste rubber has also been reutilized as additives in asphalt mixtures in the past few decades. From the environmental stand point, this alternative has been seen to be attractive, yet, it has not been extensively adopted because its implications on road life cycle cost and performance have not been conclusively established (Ganiron, 2014). The two different techniques adopted in incorporating these wastes are: 1) the wet process and 2) the dry process (Rodríguez-Fern andez et al, 2020;Tahami et al, 2019).…”
Section: Waste Rubber Tire Utilizationmentioning
confidence: 99%
“…Waste rubber has also been reutilized as additives in asphalt mixtures in the past few decades. From the environmental stand point, this alternative has been seen to be attractive, yet, it has not been extensively adopted because its implications on road life cycle cost and performance have not been conclusively established (Ganiron, 2014). The two different techniques adopted in incorporating these wastes are: 1) the wet process and 2) the dry process (Rodríguez-Fern andez et al, 2020;Tahami et al, 2019).…”
Section: Waste Rubber Tire Utilizationmentioning
confidence: 99%
“…A scalping screen will remove dirt and foreign particles. A fine harp deck screen will remove fine material from coarse aggregate [12,13]. Further cleaning is necessary to ensure the recycled concrete product is free of dirt, clay, wood, plastic and organic materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Europe, Canada, and Japan, concrete recycling is regulated and often mandated. In particular, Germany promulgated the national setting the guidelines for recycled concrete content in concrete aggregate [12]. German researchers demonstrated that recycled aggregate does not affect most performance characteristics of concrete, although it tends to increase drying shrinkage and creep, and reduce modulus of elasticity [11,12].…”
Section: Figure 1 Process Of Waste Concrete Recyclingmentioning
confidence: 99%
“…Since polymers are rather expensive, it is necessary to seek cost-effective ways to mitigate and prevent asphalt pavement premature failure [6]. In this sense, using waste rubber is viable alternative to modify bitumen due to economic and environment preservation [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the abundance and improper handled of waste rubber could cause serious environmental impact [7]. Researches on modifying bitumen with waste rubber were initiated when granular and powder forms of rubber were developed in 1930 [9].…”
Section: Introductionmentioning
confidence: 99%